E-modules of applied physics based on i-sets and context-rich problem learning (crp) approach complementary to characters: a research and development (r&d) - Yadiannur, Mitra; Rahmah, Rahmah (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2025)
This study aimed to determine the feasibility and quality of teaching e-modules developed based on the I-SETS approach and CRP Complementary Character based on aspects of media assessment, material, practicality test, and readability test on the material of equilibrium of rigid bodies. This type of development research uses the ADDIED (Analyze, Design, Develop, Implementation, Evaluation, and Disseminate) model. The research subjects involved were two media experts, two material experts, and three peer reviewers, as well as three lecturers in charge of scientific courses in physics and one lecturer with expertise in religious studies courses. The subjects for the limited trial were 11 Civil and Earth Engineering Department students. The objects studied were the feasibility of teaching E-modules, material feasibility, readability aspects, and evaluation aspects of the achievement of learning and research objectives, in this case, the practicality test of teaching e-modules. The results showed that the e-Modules of Applied Physics Teaching Based on I-SETS and Context Rich Problem Learning (CRP) Approach Complementary to Characters was said to be feasible to use in terms of media aspects with an average Aiken's V score of 0.95, Material aspects with an Aiken's V score of 0.86, practicality tests with an Aiken's V score of 0.95, and readability based on assessments by students with an Aiken's V score obtained of 0.77 and obtained a product quality score of 3.63 with an outstanding category